A novel jig arm to measure tibial plateau angle during tibial plateau leveling osteotomy. Issue 7 (22nd August 2017) - Restle, Kyle N.; Biskup, Jeffery J.
Abstract: Objective: To determine the ability of a novel device attached to the proximal tibial plateau leveling osteotomy (TPLO) jig pin to accurately predict intraoperative change in tibial plateau angle (TPA). Study design: In vitro cadaveric study. Sample population: Left hindlimbs of adult dogs (n = 9). Methods: A modified Slocum tibial plateau leveling (TPL) jig with the Rotational Osteotomy Measuring Arm (ROMA) was placed on the tibia and a radial TPLO osteotomy was performed. Based on preoperative radiographic TPA measurements, the proximal segment was rotated using the traditional method of marking points on the osteotomy a specified distance apart. After rotation, the predicted TPA was recorded based on the ROMA. Postoperative TPA was measured on radiographs. The ability of the ROMA to predict postoperative TPA was compared to that of the traditional method. Results: The average final TPA achieved with the traditional method was 6.4° (range, 3.0‐10.0°). The ROMA predicted a final TPA of 5.8° (range, 3.8‐10.1°). No significant difference was found between the TPA predicted based on the traditional method and ROMA method. Conclusion: The ROMA may be an alternative to the traditional method of measuring proximal segment rotation during TPLO procedure. Clinical relevance: Performing a TPLO with the ROMA may accurately predict the postoperative TPA while eliminating the need for measuring chord length, making reference marks, or referencing TPA charts for various osteotomy blade sizes.